Hydrolysis of Uranyl‐, Nd‐, Ce‐Ions and their Mixtures by Thermal Decomposition of Urea. Issue 4 (3rd November 2021) - Schreinemachers, Christian; Bollen, Olivier; Leinders, Gregory; Tyrpekl, Václav; Modolo, Giuseppe; Verwerft, Marc; Binnemans, Koen; Cardinaels, Thomas
Abstract: The hydrolysis of uranyl‐, Nd‐ and Ce‐cations, induced by thermal decomposition of urea was investigated and the impact of the urea content and the experiment temperature on the reaction kinetics was evaluated. Uranyl precipitated as ammonium diuranate (ADU) with varying stoichiometry. Nd(III) and Ce(III) showed comparable pH evolutions and lanthanide carbonate hydroxide ( Ln CO3 OH) products were identified, whereas Ce(IV) hydrolysed at lower pH and formed CeO2 . The precipitation behaviour was confirmed for mixtures of uranyl and the lanthanides. Depending on the urea content, a partial co‐precipitation occurred in U/Nd mixtures. The phases formed with Ce(III) and Ce(IV) were also identified in the precipitates of binary U/Ce mixtures. In ternary U/Nd/Ce compositions, a simultaneous precipitation of Nd(III) and Ce(III) was observed and a partial incorporation of the lanthanides into the ADU phase, whereas the precipitation in the presence of Ce(IV)/CeO2 led to the formation of three individual phases. Abstract : The hydrolysis of uranyl‐, Nd‐ and Ce‐ions, induced by thermal decomposition of urea was investigated for the individual cations, as well as for their binary‐ and ternary mixtures. The reaction was monitored by pH measurements, ICP‐MS and UV/Vis, and the formed precipitates were characterised with XRD and SEM.